2021
DOI: 10.31223/x55s4d
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Data Science for Geoscience: Recent Progress and Future Trends from the Perspective of a Data Life Cycle

Abstract: Data science receives increasing attention in a variety of geoscience disciplines and applications. Many successful data-driven geoscience discoveries have been reported recently, and the number of geoinformatics and data science sessions have begun to increase in many geoscience conferences. Across academia, industry, and governmental sectors, there is a strong interest to know more about the current progress as well as the potential of data science for geoscience. To address that need, this article provides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 118 publications
(128 reference statements)
0
5
0
Order By: Relevance
“…Such data‐intensive scientific pursuits will be significantly leveraged with the open data provided by OpenMindat. In our previous studies, we have also summarized experience and best practices of applying data science in geoscience, including the abductive process (Hazen, 2014), visual exploratory analysis (Ma et al, 2017) and Agile‐style datathon activities (Ma, 2022). Other scientists using OpenMindat data, if needed, may adapt those experience and best practices in their own studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such data‐intensive scientific pursuits will be significantly leveraged with the open data provided by OpenMindat. In our previous studies, we have also summarized experience and best practices of applying data science in geoscience, including the abductive process (Hazen, 2014), visual exploratory analysis (Ma et al, 2017) and Agile‐style datathon activities (Ma, 2022). Other scientists using OpenMindat data, if needed, may adapt those experience and best practices in their own studies.…”
Section: Discussionmentioning
confidence: 99%
“…The research outputs on mineral evolution and ecology (Cleland et al, 2021; Hazen et al, 2019; Hystad et al, 2015) are good examples illustrating the key components and steps in the methodology of mineral informatics. Nevertheless, the practitioners, including the authors of this paper, also found that accessing adequate reliable open data often remains a challenge for mineral informatics (Ma, 2022). Through community activities (Golden et al, 2019; Prabhu et al, 2021; Wyborn et al, 2021), although researchers are gradually improving the FAIRness (Findable, Accessible, Interoperable and Reusable) (Wilkinson et al, 2016) of open data in the field of mineralogy, more work still needs to be done to fully meet the needs of mineral informatics, particularly for machine‐to‐machine interactions (Musen, 2022; Wyborn & Brownlee, 2022).…”
Section: Introductionmentioning
confidence: 98%
“…the provider needs to share data with a small set of consumers). In essence, it becomes increasingly difficult to gauge fair pricing for a given data stream as more worker nodes cooperate to deliver the data [3][4][5].…”
Section: Problem Statementmentioning
confidence: 99%
“…The ubiquity of Social Network Services (SNS) is the result of their ability to promote virtual connectivity and boost economic and social outcomes [1][2][3]. As such, SNS platforms have become the solicited and prominent communication media enabling users to generate and share massive amount of data [3][4][5]. This data could be utilized by individuals and businesses in many different applications such as entertainment and data-driven decision-making [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation